Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum. Issue 5 (23rd February 2022) - Standish, Isaac; McCann, Rebekah; Puzach, Corey; Leis, Eric; Bailey, Jennifer; Dziki, Sara; Katona, Ryan; Lark, Ellen; Edwards, Carey; Keesler, Brandon; Reichley, Stephen; King, Stacy; et al.
Abstract: In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V .  salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C .  maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V .  salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V .  salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.